Environmental protection and developmental interests: A case study of the River Yamuna and the Commonwealth Games, Delhi, 2010. Issue 1 (2014) - ,
Abstract : Purpose – The purpose of this paper is to provide a case study of a global challenge: the relationship between commercial development and the protection of eco‐fragile systems particularly where river water is involved. It reviews and critiques the legal and political processes that underpinned the Commonwealth Games (CWG) 2010 in Delhi and the building of the accommodation Village on the floodplain of the river Yamuna.Design/methodology/approach – The paper covers the controversial modern history of the Yamuna river that runs through Delhi. The river is "dead" and has been subject to litigation concerning its usage and that of its flood plain. In particular, the controversy peaked prior to the CWG 2010 in Delhi and the required buildings associated with the games. The paper traces the history of the legal actions and the inter‐related involvement of the various actors being the politicians, construction developers, the river bank dwellers and the local environmentalists. Close analysis is made of the statutory administrative procedures required for environmental clearance, the subsequent case law both in the High Court of Delhi and the Supreme Court of India. Additionally, usage is made of the media and its concerns over corrupt and negligent practices.Findings – The Indian judiciary in their willingness to promote the construction of the Village failed to apply its own environmental jurisprudence. There was a failure to "lift the veil" and review flawed administrative practices that violated governing statutes. National pride, time pressures, political support, economic interests and rapid urbanisation created a pressure that the courts could not challenge. It was left to investigative committees, after the Games had concluded, to expose these wrongdoings.Originality/value – The paper highlights the issue of the relationship of the courts and political and economic interests and how legally protected ecological interests are ignored.